Application of Essential Facilities Doctrine to Data and Algorithm Access As An Enforcement Instrument for Article 25 of Law No. 5 Of 1999 in The Digital Economy - Dian Aryani Kusady (Journal of Law, Politic and Humanities, 2025)
Dominant digital platforms in Indonesia control strategic assets in the form of massive user data and search/recommendation algorithms that serve as market access gateways. Exclusive control over these assets creates barriers to entry and forecloses competitors in the digital ecosystem. The Essential Facilities Doctrine (EFD), traditionally applied to physical infrastructure such as ports and telecommunications networks, offers a legal framework for identifying when control over digital assets can be qualified as abuse of dominance requiring access sharing with competitors. This article doctrinally examines whether and how EFD can be applied to non-personal data and algorithms under Article 25 of Law No. 5 of 1999, and explores synchronization with Law No. 27 of 2022 on Personal Data Protection, particularly regarding data portability. The research employs a library-based approach with doctrinal-normative analysis of Law No. 5/1999 and the Data Protection Law, conceptual analysis to develop criteria for "digital essential facilities," and comparative doctrinal analysis of EFD application in the European Union and United States. Findings demonstrate that data and algorithms can be qualified as essential facilities if they cumulatively meet four criteria: (1) controlled by a dominant undertaking; (2) cannot be economically and technically duplicated; (3) access is essential for competing in downstream markets; and (4) no objective justification exists for refusing access. The article recommends that KPPU develop specific guidelines on data and algorithm access, considering efficiency defense, intellectual property rights, and privacy protection. The proposed framework balances competition enforcement with innovation incentives and clarifies when data-sharing obligations arise under Indonesian competition law without requiring legislative amendment.